Validation of an AI-Based Mitotic Counting Algorithm Trained on Breast Cancer in Soft Tissue Sarcoma, Osteosarcoma, and Melanoma: A Pilot Study - Yalcin, Ozben; Aygun, Mine Sengor; Atamanalp, Refik; Comunoglu, Cem; Tokat, Fatma; Kayhan, Cavit; Ince, Umit; Girente, Isinbike; Solmaz\\-Yilmaz, Gizem; Cayir, Sercan; Gumuskaya, Berrak; Uzel, Burak (ELSEVIER SCIENCE INC, 2025)
Annual Meeting of the United-States-and-Canadian-Academy-of-Pathology (USCAP), Boston, MA, MAR 22-27, 2025